Reclaiming Humility : Four Studies in the Monastic Tradition - Foulcher, Jane (Book collections on Project MUSE., 2015)
Does humility have a place in contemporary life? Were Enlightenment thinkers wrong to reject humility as a "monkish virtue" (Hume) arising from a "slave morality" (Nietzsche)? Australian theologian Jane Foulcher recovers the counter-cultural reading of humility that marked early Christianity and examines its trajectory at key junctures in the development of Western monasticism. Humility emerges not as a moral virtue achieved by human effort but as a way opened by grace -- as a divine "climate" (Christian de Cherge) that we are invited to inhabit. From fourth-century Egypt to twentieth-century Algeria, via Saint Benedict and Saint Bernard of Clairvaux, Dr. Foulcher's compelling analysis of theology and practice challenges the church to reclaim Christian humility as essential to its life and witness today.